Identifying african wild dog (Lycaon pictus) corridors outside Gonarezhou National Park and Save Valley Conservancy using maxent species distribution modeling - Marembo, Kudzanai Rosebud (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.